2021
DOI: 10.22434/ifamr2020.0109
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking employee’s green behavior in fertilizer industry: the role of green HRM practices and psychological ownership

Abstract: The engineering of agrochemicals and inorganic fertilizers indirectly facilitates the emissions of NO2 and CO2. The extensive use of pesticides and inorganic chemical fertilizers has drawn the world’s attention to green practices. Grounded on the ability-motivation-opportunity (AMO) theory, we investigated the effect of green human resource management (GHRM) practices on employees’ green behavior with the mediating role of psychological ownership. We applied the partial least square structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
2
7
0
5
Order By: Relevance
“…In this study, first of all, we wanted to test the direct positive effect of GHRM on work engagement levels of employees, and the results revealed that all dimensions of GHRM have a positive effect on work engagement. Our findings are parallel with previous studies showing the direct effect of GHRM on work engagement of employees (Sokro et al, 2020 ; Bhutto et al, 2021 ; Waqas et al, 2021 ). Our results revealed that the job design has the highest effect on the work engagement behavior, whereas the effect of the wage management dimension is the least.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, first of all, we wanted to test the direct positive effect of GHRM on work engagement levels of employees, and the results revealed that all dimensions of GHRM have a positive effect on work engagement. Our findings are parallel with previous studies showing the direct effect of GHRM on work engagement of employees (Sokro et al, 2020 ; Bhutto et al, 2021 ; Waqas et al, 2021 ). Our results revealed that the job design has the highest effect on the work engagement behavior, whereas the effect of the wage management dimension is the least.…”
Section: Discussionsupporting
confidence: 92%
“…Incorporating corporate environmental sensitiveness into human resources practices is explained as GHRM (Nawangsari and Sutawidjaya, 2019 ). The GHRM encompasses systems, policies, and practices necessary for developing a socially responsible, resource-efficient, and environmentally sensitive workplace (Waqas et al, 2021 ). Hence, embracing GHRM practices has become a critic strategy for those companies wherein human resources play an active part in becoming environmentally sensitive (Adriana et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we supposed that GHRM will create greater resilience and resilient individuals will fee greater work engagement. Our findings are also parallel with previous studies showing the effect of green human resources management on work engagement of employees (Bhutto et al, 2021;Waqas et al, 2021). Moreover, this study is also compatible with previous researches revealing this positive impact of work engagement on resilience (Blaique et al, 2022;Cao & Chen 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Green Human Resource Management influences elements of sustainable procurement behaviour, on the other hand, there has been a little emphasis on this topic in the literature (Jabbour et al, 2016;Waqas, Yahya, Ahmed, Rasool, & Hongbo, 2021;Zaid, Jaaron, & Talib Bon, 2018).…”
Section: Introductionmentioning
confidence: 99%